Local Promotion: Malaysia Career & Training Fair 2023 at Mid Valley - UiTM, IPSis (Institut Pengajian Siswazah (IPSis), 2023)
The Malaysia Career & Training Fair 2023 (MCTF 23) is an excellent platform for educational institutions to showcase their programs, facilities, and services to prospective students and the wider community. Such events provide an opportunity for students and parents to explore various educational options and make informed decisions about their educational journey. The primary aim of MCTF 23 is to create awareness and promote postgraduate educational opportunities that are available at Universiti Teknologi MARA (UiTM).